MODEL STRUKTURAL PENGARUH GREEN ADVERTISING DAN ECO-LABELLING TERHADAP GREEN PURCHASE INTENTION DENGAN ENVIRONMENTAL AWARENESS SEBAGAI VARIABEL MEDIASI - Fatmasari Endayani; Tri Iswari; Muhammad Rizki Firdaus; Ernita Dian Puspasari (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
This study examines the influence of green advertising and eco-labeling on green purchase intention, with environmental awareness as a mediating variable, in the context of environmentally friendly skincare products in Malang, East Java. The study aims to understand how green marketing strategies influence consumers’ purchase intentions directly and indirectly through increased environmental awareness. The novelty of this research lies in integrating green advertising and eco-labeling into a single structural model while positioning environmental awareness as the mediating mechanism within the growing green beauty industry. A quantitative survey design was employed, involving 100 consumers in Malang who had purchased or used skincare products and were familiar with environmentally friendly product claims. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess both the measurement and structural models. The results reveal that green advertising and eco-labeling significantly improve consumers’ environmental awareness and have positive direct effects on green purchase intention. Furthermore, environmental awareness positively influences purchase intention and partially mediates the relationships between green advertising, eco-labeling, and green purchase intention. These findings suggest that effective green marketing strategies enhance consumers’ purchase intentions not only through direct persuasion but also by fostering greater environmental awareness, providing valuable insights for sustainable marketing practices in the green beauty industry.